2022
DOI: 10.3390/antibiotics11081119
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Molecular Features Associated with Persistent and Relapsing Staphylococcus aureus Prosthetic Joint Infection

Abstract: Background: Persistent and relapsing prosthetic joint infection (PJI) due to Staphylococcus aureus presents a clinical challenge. This study aimed to provide an extensive description of phenotypic and genomic changes that could be related to persistence or relapse. Methods: Initial and second S. aureus isolates from 6 cases of persistent and relapsing PJI, along with clinical isolates from 8 cases, with favorable outcome were included. All isolates were studied by phenotypic and genotypic approaches. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The third study, using the analysis of WGS data did not show any differences between genome analysis and outcomes in patients with PJI [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The third study, using the analysis of WGS data did not show any differences between genome analysis and outcomes in patients with PJI [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported outcomes of severity of infection [ 25 , 27 ] or determinants of chronic infection [ 24 , 31 , 36 ], whereas nine other studies used different definitions of outcome for failure, recurrence, or success [ 26 , 28 , 29 , 30 , 32 , 33 , 34 , 35 , 37 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations